(3GdadSaI GdYedjI YfO eGQchS ChQjdjhS (B: s (3OQGSI JMdjdjI dcJGH GdJCedGJ (B= Practical philosophy of Marcus Aurelius , An analytical study of meditations / s - (3MehO cGed TQja YHOGddg GdaVdis; (3Cjef CMeO (B: s; (3eUWai GdfTGQ (B: s ((3GdbGgQI (B: s (3MehO cGed TQja YHOGddg GdaVdi (B: s, 2017)
(3JbOe gPg GdOQGSI JMdjd edGeM GdadSaI GdYedjI h GdJWHjbjI YfO GdCeHQGWhQ GdQheGfi h GdajdSha GdQhGbi eGQchS ChQjdjhS GdJi YHQ YfgG ai cJGH (B"(3GdJCedGJ(B" (3Ch (B"(3Gdi GdPGJ(B" (3ceG ai GddZI GdjhfGfjI(B. (3h JSdW gPg GdOQGSI GdVhA Ydi GdLhGfH GdTNUjI dMjGI eGQchS(B: (3h Cge GdCMOGK GdJGQjNjI GdJi JQcJ CKQG ai adSaJg(B: (3h GdCTNGU GdPjf CKQhG h JCKQhG HacQI(B. (3NdGd gPG GdYed Sha fSJYQV CQGA GdajdSha eGQchS ai GdPGJ h Gdchf h GdeOjfI GdYGdejI h eaghe GdMcje GdQhGbi(B. (3h CjVG eUjQ GdfaS h GdNjQ h GdTQ h GdbOQ h GdMQjI h GdYfGjI GdCdgjI h GddMXI GdCdjI h GdeOGNdI h eaGgje h eUWdMGJ CNQi PcQgG h JfGhdgG ChQjdjhS ai JCedGJg HMSH eG jJfGSH eY gOa GdHMK h ZGjJg(B. (3h cPdc JMGhd GdOQGSI Cf JdeS GdCKGQ GdQhGbjI GdjhfGfjI ai GdeLJeY GdQheGfi h NGUI Ydi GdbGfhf GdQheGfi(B. (3aEPG cGf GdjhfGfjhf jacQhf HWQjbI CNdGbjI(B. (3aEf GdQheGf jacQhf HWQjbI MbhbjI bGfhfjI(B. (3ceG JMGhd gPg GdOQGSI GdELGHI Yf JSGDdGJ YOI efgG(B: (3gd JMbb GdMde GdCadGWhfi HhUhd GdajdSha Ydi GdYQT? h eOi fLGM Pdc? h gd GdSjGSI JaSO GdadSaI? Ce GdadSaI Jbhe GdSjGSI? h gd YdGbI GdajdSha jGdSjGSI fYeI Ce fbeIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdadSaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdadSaI GdYedjIs; (3cJGH GdJCedGJ s; (3eGQchS ChQjdjhS s